PENEGAKAN HUKUM DALAM MENANGGULANGI DAMPAK ISLAMOPHOBIA TERHADAP KERUKUNAN UMAT BERAGAMA DI WILAYAH HUKUM KEPOLISIAN DAERAH BALI - Primadya, Muhammad Ghana Elang (Kerta Dyatmika, 2025)
The phenomenon of Islamophobia in Bali may be triggered by misunderstanding, prejudice, and discriminatory actions against Muslims. In the context of Bali’s rich cultural and religious diversity, wise and proactive management is essential to maintain interfaith harmony and prevent potential conflicts. This study aims to analyze the impact of Islamophobia on religious harmony within the jurisdiction of the Bali Regional Police and to examine the legal enforcement measures implemented to mitigate such impacts. The research adopts an empirical juridical method with a descriptive approach, involving direct data collection from field informants. The findings reveal that Islamophobia has broad implications across various sectors, including economic, social, religious practice, political, and educational domains. In the economic sphere, Muslims may face restrictions in conducting business activities; socially, they may experience discrimination during everyday interactions; and in terms of religious practices, obstacles arise in establishing places of worship, such as mosques. Law enforcement efforts include a community-based approach, whereby the Bali Regional Police collaborate with religious leaders and community figures to identify and address issues before escalation, incorporating interfaith dialogue and activities that foster mutual understanding and tolerance. In addition, preventive legal measures involve public education and awareness campaigns aimed at reducing stigma and strengthening intergroup relations. In conclusion, collaborative and preventive strategies serve as effective legal mechanisms to uphold religious harmony amid the challenges posed by Islamophobia in Bali.